GenBank population set information - Searle, Jeremy; Martínková, Natália; Barnett, Ross; Cucchi, Thomas; Struchen, Rahel; Pascal, Marine; Pascal, Michel; Fischer, Martin; Higham, Thomas; Brace, Selina; Ho, Simon; Quere, Jean-Pierre; et al. (Dryad Digital Repository, 2013)
Ancient DNA sequences of cytb from common voles, Microtus arvalis, are in GenBank under PopSet: 302202495. Modern complete sequences of the cytb gene from common voles, Microtus arvalis, are in GenBank under PopSet: 304634227.